Interaction of Polyamines, Abscisic Acid, Nitric Oxide, and Hydrogen Peroxide under Chilling Stress in Tomato (Lycopersicon esculentum Mill.) Seedlings - Diao, Qiannan; Song, Yongjun; Shi, Dongmei; Qi, Hongyan (Frontiers in Plant Science, 2017)
Polyamines (PAs) play a vital role in response to abiotic stress of higher plants. However, limited studies examined the interplay between PAs and signal molecules. Therefore, in this study, we tried to elucidate the crosstalk between PAs, abscisic acid (ABA), nitric oxide (NO) and hydrogen peroxide (H2O2) under chilling stress conditions were determined using tomato seedlings (Lycopersicon esculentum Mill.) cv. Moneymaker). The study showed that during chilling stress (4 oC, 0 h, 12 h and 24 h), application of Spd and Spm could elevate NO and H2O2 levels, enhance nitrite reductase (NR), nitric oxide synthase (NOS)-like, and polyamine oxidase (PAO) activities, upregulate LeNR relative expression, but did not influence LeNOS1 expression. While putrescine (Put) treatment had no this obvious impact in tomato leaves. Moreover, H2O2 might act as an upstream signal to stimulate NO production under chilling stress. In recovery period (25/15 oC, 10 h), above-mentioned parameters induced by PAs application were back to the control levels. In turn, seedlings pretreated with sodium nitroprusside (SNP, an NO donor) improved Put and Spd levels through increasing arginine decarboxylase (LeADC, LeADC1), ornithine decarboxylase (LeODC) and Spd synthase (LeSPDS) expressions in tomato leaves throughout treatment period. Put content appeared increases first, and then Spd content began to rise under chilling stress. Exogenously applied NO did not improved S-adenosylmethionine decarboxylase (LeSAMDC) and Spm synthase (LeSPMS) expressions, which led to constant Spm level under chilling stress and recover period. On the other hand, exogenous Put significantly increased ABA content and LeNCED1 transcript level, ABA treatment could alleviate the electrolyte leakage (EL) induced by D-arginine (D-Arg, an inhibitor of Put). Taken together, it is concluded that Spd and Spm enhanced NO production in tomato seedlings in H2O2-dependent way under chilling stress, which through NR and NOS pathways. ABA is involved in Put induced chilling stress tolerance. Furthermore, NO could improve the Put and the Spd contents under chilling stress.